Teodor Duracz (1883–1943). Szkic do portretu - Ruzik, Konrad (Komunizm: System - Ludzie - Dokumentacja, 2013)
The theme of the article is Teodor Duracz, one of the activists of the Communist Party of Poland and the Polish Workers Party (PWP). Born in 1883, in Charków, in 1905 he joined the Polish Socialist Party (PPS), after the break-up in 1906, belonged to the PPS-Left. Since 1918, residing in Warsaw. Related Polish Communist Party (KPP), being an lawyer of education defended the Polish communist activists before the courts and collaborated with Soviet intelligence. In the years 1922–1937 he was general counsel of the dealership USSR in Warsaw. He has also collaborated with International Organization for Aid Revolutionists (MOPR) created by the III International Socialist (The Comintern). In 1941, he was an activist of the Communist underground groups "Proletarian". In 1942, he was one of the organizers of the Polish Workers Party (PWP ). At the end of this year, was the head of the group leading the internal investigation into the circumstances of the murder of Marceli Nowotko, Secretary PWP. In 1943, arrested by the Germans in Warsaw, died at Pawiak as a result of torture used against him during the investigation.